A relação entre o Programa Mulheres Mil e a tecnologia social como uma estratégia de formação profissional - Ponciano, Roberta Rodrigues (2022)
Programa Mulheres Mil (PMM in Portuguese abbreviation), developed in several Brazilian educational institutions and created through MEC Decree n. 1015, of July 21st, 2011 (BRASIL, 2011b), is a professional training policy described in some official documents as Social Technology (ST) and a tool for expanding knowledge, development and opportunities for insertion in the world of work. In this context, strategies for capturing and benefiting a certain social class, through the development of professional training called TS, are formed by contradictions and values to foster these women interested in change and who intend to attend courses in an attempt to ensure the realization of their purposes, whether in education and/or in the world of work. In this way, the present thesis aims to analyze the PMM from the point of view of professional training policy and its relationship with the conceptions of STs, in addition to verifying the implications for education and the world of work – here similarities with the concept of ST and the contradictions that involve them in this conjuncture. The research refers to a qualitative approach of a bibliographic, documentary and descriptive nature, whose analyzed phenomena correspond to the results and to the existing correlations between the PMM and the ST, as well as the context in which such actions were developed, that is, the world of work in the Brazilian reality. The results indicate that the PMM needs to be reformulated to be a ST, as some actions and directions at the beginning of this initiative, such as the active participation of women in the construction of the project and the respective evaluation, were strongly related to the characteristics of the ST, but still would need adjustments for their involvement in the full creation of the PMM. It is worth mentioning that, even with the insertion of the PMM in the National Program for Access to Technical Education and Employment (PRONATEC in Portuguese abbreviation), the situation worsened, since the specific considerations aimed at the target audience of the proposal, such as teachers prepared to meet the demand, ceased to exist and became more generalist – however, some products arising from professional training with the participation of women could be preliminarily listed as ST. In fact, approaching ST requires different knowledge so as not to confuse it with another type of technology or artifact, as many people do not have knowledge on the subject and consider it an alternative to the incipient informality in certain places. On the other hand, and in other areas, the concept is adequately consolidated, such as the cisterns that have become public policies and the solidarity economy, with the development of various social technologies that direct and enhance collaborative activities in various fields (consumption, production, joint marketing, services, finance and technological development and organization of collaborative networks). At the same time, STs are human and educational activities, in which individuals perform them through work in the relationship with other individuals and nature to produce a tool that seeks to provide social emancipation and solutions to another mode of production without being subordination. to degrading means and expropriation of workers’ strength and knowledge.